2017
DOI: 10.1512/iumj.2017.66.6038
|View full text |Cite
|
Sign up to set email alerts
|

Ueda theory for compact curves with nodes

Abstract: Abstract. Let C be a compact complex curve included in a non-singular complex surface such that the normal bundle is topologically trivial. Ueda studied complex analytic properties of a neighborhood of C when C is non-singular or is a rational curve with a node. We propose an analogue of Ueda's theory for the case where C admits nodes. As an application, we study singular Hermitian metrics with semi-positive curvature on the anti-canonical bundle of the blow-up of the projective plane at nine points in arbitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…In this case, K −1 X Z is semi-positive by a standard argument (see §2.1). In [K4], we showed that the conditions (i), (iii) and (iv) in Theorem 1.2 hold if α(N Z ) = e 2π √ −1θ holds for some Diophantine irrational number θ [K4,Theorem 1.4,Corollary 7.5]. Here we say that an irrational number θ is Diophantine if there exist positive numbers A and α such that min n∈Z |n − mθ| ≥ A • m −α .…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…In this case, K −1 X Z is semi-positive by a standard argument (see §2.1). In [K4], we showed that the conditions (i), (iii) and (iv) in Theorem 1.2 hold if α(N Z ) = e 2π √ −1θ holds for some Diophantine irrational number θ [K4,Theorem 1.4,Corollary 7.5]. Here we say that an irrational number θ is Diophantine if there exist positive numbers A and α such that min n∈Z |n − mθ| ≥ A • m −α .…”
Section: Introductionmentioning
confidence: 98%
“…As nothing is unclear on (singular) Hermitian metrics on K −1 X Z if it is not nef (see [K4, §7]), we assume that K −1 X Z is nef. Then, according to [K4,Proposition 7.10], there exists a reduced divisor Y Z ∈ |K −1 X Z | such that the restriction K −1 X Z | Y Z admits a flat connection (i.e. all the transition functions are C * -constant for a suitable choice of local trivializations) and that Y Z is the strict transform of either a smooth elliptic curve, a cycle of rational curves, a curve with a cusp, or three lines intersecting at a point of P 2 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations